Pragmatics - Yule, George (Oxford Oxford University Press, 2020)
This book outlines pragmatics, the study of how people make sense of each other linguistically. Basic concepts such as the cooperative principle, deixis, and speech acts are explained and illustrated, providing readers with an ideal foundation for further study.
Keywords: Cơ bản